Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/nature14457
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of bidirectional COPI transport at the Golgi by CDC42

Abstract: The Golgi complex plays a central role in the intracellular sorting of secretory proteins 1,2. Anterograde transport through the Golgi has been explained by the movement of Golgi cisternae, known as cisternal maturation 3–5. Because this explanation is now appreciated to be incomplete 6, interest has developed in understanding tubules that connect the Golgi cisternae 7–9. Here, we find that the Coat Protein I (COPI) complex sorts anterograde cargoes into these tubules. Moreover, the small GTPase cdc42 regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 25 publications
7
92
1
Order By: Relevance
“…A C-terminal valine residue, which is common in type I membrane proteins, has also been proposed to serve as an anterograde signal by associating with Golgi matrix proteins (GRASP65 and -55) (D'Angelo et al 2009). Finally, COPI acting in concert with CDC42 may promote forward transport in the Golgi complex by targeting cargo to tubular Golgi elements (Park et al 2015).…”
Section: Retrograde Sorting Signals and Receptorsmentioning
confidence: 99%
“…A C-terminal valine residue, which is common in type I membrane proteins, has also been proposed to serve as an anterograde signal by associating with Golgi matrix proteins (GRASP65 and -55) (D'Angelo et al 2009). Finally, COPI acting in concert with CDC42 may promote forward transport in the Golgi complex by targeting cargo to tubular Golgi elements (Park et al 2015).…”
Section: Retrograde Sorting Signals and Receptorsmentioning
confidence: 99%
“…Following up on this discovery, a recent study has found that Cdc42 not only inhibits the sorting of retrograde cargoes into COPI vesicles, but also promotes the formation of COPI tubules to enhance anterograde Golgi transport [24]. Although vesicle and tubule formation are both initiated by the formation of COPI buds from Golgi membrane, vesicle formation involves the subsequent constriction of the bud neck that eventually results in vesicles being released from organellar membrane, a process known as vesicle fission.…”
Section: The Golgi Pool Acts Independently Of the Plasma Membrane Poolmentioning
confidence: 99%
“…This observation suggests that the DxE motif in the cytosolic tail, in addition to being responsible for VSVG recruitment to ERES (Nishimura and Balch, 1997;Sevier et al, 2000), also plays a role in driving the progression of VSVG through the Golgi. Recently, five basic residues upstream of the DxE motif have been shown to favor the transport of VSVG through the Golgi through a COPI-CDC42-regulated pathway (Park et al, 2015).…”
Section: Lipid-dependent Sortingmentioning
confidence: 99%